2012
DOI: 10.5194/angeo-30-983-2012
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characteristics and scatter cross-section of low latitude mesospheric echoes measured by the Indian MST radar at Gadanki

Abstract: Abstract. In November 2008 and in March and April 2009the Indian MST radar (53 MHz) at Gadanki was operated during the daytime in a special experiment, with 600 m altitude resolution, for understanding the characteristics of lowlatitude mesospheric echoes (LLME). The data of three days when the echoes were strongest have been analysed in terms of spectral widths and radar volume reflectivities. Spectral widths of LLME show some decrease with altitude, with median values of 4-6 m s −1 at 69-72 km and of 2-4 m s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…[] and Belova et al . []. Figure shows the GSM cosmic noise along with the MST radar observed noise at 53 MHz (after properly scaling up) over Gadanki on different days and in different months as a function of sidereal time.…”
Section: Computation Of Reflectivity and Turbulence Parameterssupporting
confidence: 89%
See 2 more Smart Citations
“…[] and Belova et al . []. Figure shows the GSM cosmic noise along with the MST radar observed noise at 53 MHz (after properly scaling up) over Gadanki on different days and in different months as a function of sidereal time.…”
Section: Computation Of Reflectivity and Turbulence Parameterssupporting
confidence: 89%
“…To account for the noise variation, the Global Sky Model (GSM) [de Oliveira-Costa et al, 2008] has been used to calculate the galactic noise contribution to T noise at 53 MHz over Gadanki. The contribution of galactic cosmic noise has been calculated as a function of time for all the days of observations following Kirkwood et al [2010] and Belova et al [2012]. Figure 2 shows the GSM cosmic noise along with the MST radar observed noise at 53 MHz (after properly scaling up) over Gadanki on different days and in different months as a function of sidereal time.…”
Section: Volume Reflectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Turbulence is generated either by convective or dynamical instability depending on the background temperature and wind fields. Radar observations have also revealed that the low‐latitude mesospheric echoes could be linked with turbulent layer and/or spatially confined patchy regions [e.g., Royrvik , ; Sheth et al ., ; Lehmacher et al ., ; Chandra et al ., ; Belova et al ., ]. The descending layer‐type morphology of the echoing regions, which indicate the potential role of tidal/gravity wave dynamics on the echoing morphology, however, have not been paid attention so far.…”
Section: Introductionmentioning
confidence: 99%